Respuesta :

Answer:

[tex]18x^2+85x+18 = 0[/tex]

Step-by-step explanation:

Given Equation is

=> [tex]2x^2+7x-9=0[/tex]

Comparing it with [tex]ax^2+bx+c = 0[/tex], we get

=> a = 2, b = 7 and c = -9

So,

Sum of roots = α+β = [tex]-\frac{b}{a}[/tex]

α+β = -7/2

Product of roots = αβ = c/a

αβ = -9/2

Now, Finding the equation whose roots are:

α/β ,β/α

Sum of Roots = [tex]\frac{\alpha }{\beta } + \frac{\beta }{\alpha }[/tex]

Sum of Roots = [tex]\frac{\alpha^2+\beta^2 }{\alpha \beta }[/tex]

Sum of Roots = [tex]\frac{(\alpha+\beta )^2-2\alpha\beta }{\alpha\beta }[/tex]

Sum of roots = [tex](\frac{-7}{2} )^2-2(\frac{-9}{2} ) / \frac{-9}{2}[/tex]

Sum of roots = [tex]\frac{49}{4} + 9 /\frac{-9}{2}[/tex]

Sum of Roots = [tex]\frac{49+36}{4} / \frac{-9}{2}[/tex]

Sum of roots = [tex]\frac{85}{4} * \frac{2}{-9}[/tex]

Sum of roots = S = [tex]-\frac{85}{18}[/tex]

Product of Roots = [tex]\frac{\alpha }{\beta } \frac{\beta }{\alpha }[/tex]

Product of Roots = P = 1

The Quadratic Equation is:

=> [tex]x^2-Sx+P = 0[/tex]

=> [tex]x^2 - (-\frac{85}{18} )x+1 = 0[/tex]

=> [tex]x^2 + \frac{85}{18}x + 1 = 0[/tex]

=> [tex]18x^2+85x+18 = 0[/tex]

This is the required quadratic equation.

Answer:

α/β= -2/9      β/α=-4.5

Step-by-step explanation:

So we have quadratic equation  2x^2+7x-9=0

Lets fin the roots  using the equation's  discriminant:

D=b^2-4*a*c

a=2 (coef at x^2)   b=7(coef at x)  c=-9

D= 49+4*2*9=121

sqrt(D)=11

So x1= (-b+sqrt(D))/(2*a)

x1=(-7+11)/4=1   so   α=1

x2=(-7-11)/4=-4.5    so  β=-4.5

=>α/β= -2/9       => β/α=-4.5